A comparison between Deep Learning architectures for the assessment of breast tumor segmentation using VSI ultrasound protocol - (:unkn) unknown (IEEE, 2024)
Automatic breast tumor ultrasound segmentation is one of the most critical components in the development of tools for breast cancer diagnosis. Several deep learning algorithms have been tested with public and private datasets but none of them has been de...
Keywords: Segmentación de tumores; Aprendizaje profundo